MECHANICAL PROPERTIES OF DISCONNECTED MULTIWALLED CARBON NANOTUBES AND CARBON NANOTUBE COMPOSITES - A REVIEW PAPER - Randjbaran, Elias; Zahari, Rizal; Majid, Dayang L.; Sultan, Mohamed T. H.; Mazlan, Norkhairunnisa (International Journal of Research -GRANTHAALAYAH, 2018)
Motivation/Background: Current review paper is about the forecast of Young’s modulus for carbon nanotubes, from both hypothetical and exploratory angles are introduced. The disparities between the estimations of Young’s modulus announced in the writing are broke down, and distinctive patterns of the outcomes are examined. Explain the importance of the problem investigated in the paper. Include here a statement of the main research question. Method: A whole investigation is performed to feature the obstructions and downsides of the demonstrating methods and crucial presumptions utilized which ought to be defeated in additionally contemplates. Conclusions: The perspectives that ought to be considered all the more precisely in demonstrating carbon nanotube composites are distinguished.